Interaction Mechanism of Fe with Dietary Fiber Component at in vitro Gastrointestinal System Condition - Leny Yuanita (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
The aim of the research was to describe the interaction mechanism of Fe with yard long bean dietary fiber macromolecules at gastrointestinal system in-vitro, through the combination of acidity and boiling time. The research based on the factorial experimental design, with two independent variables, i.e. acidity medium (pH 3, 4, 5, 6, 7)and boiling time (0/raw, 5, 20, 35 minutes). Dependent variables were iron binding percentage, effective stability constants (Keff), and adsorption constants (Kads). Scatchard and Langmuir graph methods through Keff and Kads were then applied to determine the mechanism of iron interaction. The results of the research showed that the highest binding Fe by dietary fiber at pH 7- raw, and lowest at pH 3- boiling time 35 minutes. The iron binding pattern by dietary fiber at gastrointestinal system is through formation of complex compound that more prominent than physically adsorption, and involved two types of specific binding sites, one of which showed a higher affinity than the other.